The Role of Strategic Management in Dealing with Risks Facing Companies: An Analytical Study in the Kingdom of Saudi Arabia – 2025 - Natheer, Hanan Abdullah (Journal of Risk and Crisis Management, 2025)
This study aimed to analyze the pivotal role of strategic management in addressing the increasing risks facing companies in the Kingdom of Saudi Arabia during 2025, and how this contributes to achieving the objectives of Vision 2030. To achieve this goal, the research adopted a descriptive-analytical methodology, based on a review of relevant literature and a field study conducted through a questionnaire distributed to a random sample of 89 employees in Saudi companies, with data analyzed using SPSS. The main findings revealed a strong, positive correlation between the application of strategic management (with its two dimensions: strategic planning and strategic analysis) and the ability to manage risks, as strategic management explained 33.8% of the variance in risk management effectiveness. The results showed that companies place a high emphasis on strategic planning, while the level of strategic analysis remains moderate. Based on these findings, the study recommended the necessity of integrating risk management as an integral part of the companies’ overall strategy, developing robust contingency plans, investing in advanced technology and continuous employee training, fostering a corporate culture that encourages transparency and learning from mistakes, and enhancing collaboration with external stakeholders to effectively manage shared risks.